Frequencies of Micronucleus in Mononucleated Cells of People Living in Takandeang Village – A High Level of Natural Radiation Area in Indonesia - Purnami, Sofiati; Lubis, Masnelli; Suryadi, Suryadi; Nurhayati, Siti; Ramadhani, Dwi; Syaifudin, Mukh (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2018)
Our previous study showed that the micronucleus frequencies of Botteng Village inhabitants in Mamuju (a high background radiation area) were higher compared to control samples even though the difference was not significant. To validate our previous study result, here in this study we assessed the micronucleus frequencies in mononucleated cells of Takandeang Village inhabitants. Twenty seven healthy adult subjects from Takandeang Village and normal background radiation area were included in this study. Micronucleus numbers (MN) in 1000 mononucleated cells (MNC) were evaluated in this study. Results showed that mean MN numbers in MNC (MNMNC) of Takandeang Village inhabitants were significantly higher compared to control samples [3.96 ± 0.488 vs 1.96 ± 1.675; p<0.05]. The age and gender factors did not affect the MNMNC in all samples (p>0.05). It is possible that the high background radiation exposure received by Takandeang Village inhabitants induced not only the clastogenic but also aneugenic effect in lymphocytes. Overall our study showed that scoring of MNMNC can provide additional information in cytokinesis block micronucleus (CBMN) assay. Further study should be performed to validate this study results. The 24 hours culture time should be used in the further study to obtain more comprehensive results.